Aligned human cardiac syncytium for in vitro analysis of electrical, structural, and mechanical readouts. Issue 1 (13th October 2020) - Napiwocki, B. N.; Lang, D.; Stempien, A.; Zhang, J.; Vaidyanathan, R.; Makielski, J. C.; Eckhardt, L. L.; Glukhov, A. V.; Kamp, T. J.; Crone, W. C.
Abstract: Human pluripotent stem cell‐derived cardiomyocytes (hPSC‐CMs) have emerged as an exciting new tool for cardiac research and can serve as a preclinical platform for drug development and disease modeling studies. However, these aspirations are limited by current culture methods in which hPSC‐CMs resemble fetal human cardiomyocytes in terms of structure and function. Herein we provide a novel in vitro platform that includes patterned extracellular matrix with physiological substrate stiffness and is amenable to both mechanical and electrical analysis. Micropatterned lanes promote the cellular and myofibril alignment of hPSC‐CMs while the addition of micropatterned bridges enable formation of a functional cardiac syncytium that beats synchronously over a large two‐dimensional area. We investigated the electrophysiological properties of the patterned cardiac constructs and showed they have anisotropic electrical impulse propagation, as occurs in the native myocardium, with speeds 2x faster in the primary direction of the pattern as compared to the transverse direction. Lastly, we interrogated the mechanical function of the pattern constructs and demonstrated the utility of this platform in recording the strength of cardiomyocyte contractions. This biomimetic platform with electrical and mechanical readout capabilities will enable the study of cardiac disease and the influence of pharmaceuticals and toxins on cardiomyocyte function. The platform also holds potential for high throughput evaluation of drug safety and efficacy, thus furthering our understanding of cardiovascular disease and increasing the translational use of hPSC‐CMs. Abstract : A biomimetic cell culture platform that combines micropatterning with a physiologically relevant substrate stiffness was used with cardiomyocytes derived from pluripotent stem cells (hPSC‐CMs) to promote elongation and alignment of their internal cytoarchitecture and results in anisotropic conduction. This cell culture platform enables structural, mechanical, and electrical measurements to be made. Such multiparametric readouts are essential in order to increase the therapeutic and clinical relevance of hPSC‐CMs.